KEABSAHAN PENJAMINAN HAK MILIK ATAS TANAH YANG DIDASARKAN PADA AKTA DI BAWAH TANGAN (STUDI KASUS PUTUSAN NOMOR 53/PDT.G/2017/PN.SGN) - Akbar Rahadianto; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2018)
Land rights guarantee is a guarantee made by the debtor to the creditor which generally aims to obtain a loan in the form of money for the debtor and repayment of debt to the creditor. In the case of guaranteeing land rights, the procedure has been regulated in the Underwriting Rights on land along with land-related objects act. In this act, it is explained that in the case of guaranteeing land rights, it must be made in an authentic deed named deed of mortgage. But in this case the debtor guarantees ownership rights of the land to the creditor with only deed under hand, not with the deed of mortgage. Is the guarantee still valid? and how about the executorial power? In this study the author uses a case approach and legislative approach. It can be concluded that the guarantee of ownership rights on land based on the deed under the hand is valid because it has fulfilled the elements of Article 1320 of the Civil Code concerning the legal requirements of the agreement. Then for the execution strength, it can be done, but it will be very difficult because it requires a court order to execute the collateral object. The suggestion from the author is that in guaranteeing the rights to the land, it must be charged the Deed of mortgage, so that if there is a default, the execution of the guarantee object is easy and does not take a long time.